Development of Technical Drawing Module Based On Projection and Sectional Views Equipped with Lego Block Assembly Media Assistance - Agung Prijo Budijono; Wahyu Dwi Kurniawan; Arda Widyatama (Journal of World Conference (JWC), 2019)
. This research is motivated by the lack of practical learning media in the discussion of projections and pieces in the learning process of technical drawing courses. Referring to the discussion, the researcher made a module "Teaching Drawing Technique Module Main Subjects of Projection and Pieces Equipped with Information Technology Lego Viewer Media Assistance" which later will be a support in the learning process so as to help students individually achieve learning goals in a learning process. Learning media that will be applied in engineering drawing courses, will later be developed using the 4-D development model (four D models) which consists of 4 stages, namely: (1) Define, (2) Design, (3) Development , and (4) Disseminate. The defining stage includes the initial analysis, student analysis, concept analysis, task analysis, and specification of learning objectives. The design phase consists of the preparation of tests, media selection, format selection, and initial design (initial design). At the development stage it consists of module validation by expert lecturers, student response questionnaires, and about the pretest posttest for students. Whereas the deployment is not carried out due to the limited time of the study. The results showed (1) the module products developed were very feasible to use (2) students showed a positive response to the module developed (3) student learning outcomes improved with good categories.